Lithium metal battery and method for preparing lithium metal used in the preparation of lithium metal anodes
Patent Information
- Application Number
- CN202610197358.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-28
- Filing Date
- 2026-02-11
- Publication Date
- 2026-10-30
AI Technical Summary
[0009]然而,在锂金属电池内添加能够抑制锂枝晶生长的聚合物膜的研究的缺点在于锂离子电导率根据聚合物膜的形态而降低,并且由于聚合物的机械性能而不能完全地抑制锂枝晶生长
[0034]根据实施方案的锂金属电池包括与负载添加剂锂盐的多孔聚合物载体膜一体化的锂金属负极,即使在溶解度极低的溶剂中也可以连续地溶出微量锂盐并产生电化学作用,从而能够显著改进锂金属电池的循环寿命特性。
Smart Images

Figure CN123018056A_ABST
Abstract
Description
[0001] Cross-references to related applications This application claims priority and benefit to Korean Patent Application No. 10-2025-0055406, filed with the Korean Intellectual Property Office on April 28, 2025, the entire contents of which are incorporated herein by reference. Technical Field
[0002] This invention relates to a lithium metal battery comprising a lithium metal anode integrated with a polymer carrier membrane for use in lithium metal batteries, and a method for preparing lithium metal for use in the lithium metal anode. Background Technology
[0003] Electric vehicles can use high-capacity batteries that exceed the capacity of lithium-ion batteries. Therefore, it is desirable to have anode and cathode materials with high energy density, and lithium metal batteries with high energy density and long-term stability.
[0004] Therefore, lithium metal (which has a high specific capacity of 3860 mAh / g and a low standard electrode potential (-3.04 Vvs standard hydrogen electrode)) has attracted attention as a negative electrode material for rechargeable lithium batteries.
[0005] Lithium metal batteries are rechargeable batteries that use lithium metal as the negative electrode material. Lithium metal (which has a specific capacity 10 times higher than graphite, used as the negative electrode in rechargeable lithium batteries, but with a low reduction potential) is a promising material for the negative electrode of high-energy-density rechargeable batteries. Various studies are underway on the practical use of lithium metal as the negative electrode material to commercialize these lithium metal batteries.
[0006] However, during charging and discharging, lithium dendrites may grow on the lithium anode, causing it to degrade. This not only reduces battery capacity and cycle life but also leads to short circuits between the anode and cathode, resulting in safety issues. Furthermore, the high reactivity of lithium metal causes the decomposition of the liquid electrolyte, forming an unstable insulating film with low mechanical strength and high ionic resistance on the lithium anode surface. This unstable film may not only inhibit further decomposition of the liquid electrolyte but also impede lithium-ion conduction, thus reducing battery capacity and cycle life.
[0007] To address this issue, various studies have been conducted (e.g., coating lithium surfaces with ferroelectric polymers to suppress lithium dendrite growth, applying chemical reactions to dissociate substances that are limited in their use due to low solubility in carbonate electrolytes, and finding electrolyte compositions and additives for lithium metal batteries to form stable films on lithium metal surfaces, etc.) to improve the characteristics of lithium metal batteries by modifying the lithium anode surface and electrolyte.
[0008] In other words, in order to commercialize lithium metal batteries, active research is being conducted by adding polymer films to lithium metal batteries and diversifying and optimizing the composition of the electrolyte (e.g., solvents, lithium salts, additives, etc.).
[0009] However, the drawback of research on adding polymer films that can suppress lithium dendrite growth into lithium metal batteries is that the lithium-ion conductivity decreases depending on the morphology of the polymer film, and lithium dendrite growth cannot be completely suppressed due to the mechanical properties of the polymer.
[0010] Furthermore, research exploring new electrolyte components for lithium metal batteries by studying solvents, lithium salts, and additive dosages has a drawback: the types of lithium salts and additives are limited, and their solubility varies significantly depending on the electrolyte solvent. In particular, when additive lithium salts, which are continuously consumed during lithium metal battery operation, are included in the electrolyte composition, capacity and cycle life characteristics may rapidly decline after all additive lithium salts are consumed.
[0011] The statements in this background section are provided only as background information in relation to the present invention and may not constitute prior art. Summary of the Invention
[0012] One aspect of the present invention provides a method for preparing lithium metal integrated with a polymer carrier membrane and a lithium metal battery comprising the lithium metal prepared by the method as a lithium metal anode, wherein the polymer carrier membrane stores additive lithium salts capable of improving the performance of the lithium metal battery.
[0013] The lithium metal battery according to the embodiment includes: a positive electrode, a lithium metal negative electrode opposite to the positive electrode, and a separator located between the positive electrode and the negative electrode. The lithium metal negative electrode is integrated with a porous polymer carrier membrane, the porous polymer carrier membrane being loaded with an additive lithium salt.
[0014] The additive lithium salt may include at least one or any combination thereof from LiNO3, lithium difluoro(oxalate)borate (LiDFOB), LiBOB (lithium di(oxalate)borate), LiPO2F2, LiPF6, LiBF4, LiN(SO2F)2, LiN(SO2C2F5)2, LiCF3SO3, LiC4F9O3, LiC6H5SO3, LiSCN, LiB(C2O4)2, and LiDFOP (lithium difluoro(oxalate)phosphate).
[0015] The porous polymer carrier membrane may also contain a polymer, and the polymer may include at least one or any combination of poly(vinylidene fluoride-hexafluoropropylene) copolymer (PVdF-HFP), polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), polymethyl methacrylate (PMMA), polyethylene oxide (PEO), polypropylene (PP), polyimide (PI), polyamide-imide (PAI), polystyrene (PS), polyvinyl chloride (PVC), polyether ether ketone (PEEK), and polyester sulfone (PES).
[0016] The thickness of the porous polymer carrier membrane can be less than or equal to 5 μm.
[0017] Based on the total amount (100 wt%) of the porous polymer carrier membrane, the additive lithium salt may be included in an amount ranging from 2 wt% to 20 wt%.
[0018] The thickness of lithium metal anodes can range from 5 μm to 200 μm.
[0019] A lithium metal anode integrated with a porous polymer support membrane loaded with lithium salt additives may include: a current collector, a lithium metal layer on the current collector, and a porous polymer support membrane, wherein the porous polymer support membrane is loaded with lithium salt additives and is located on the surface of the lithium metal layer. The lithium metal layer and the porous polymer support membrane may be integrated.
[0020] The thickness of the lithium metal layer can be greater than that of the current collector, and the thickness of the current collector can be greater than that of the porous polymer carrier film.
[0021] The additive lithium salt may include a first additive lithium salt and a second additive lithium salt. The first additive lithium salt may include LiNO3. The second additive lithium salt may include at least one or any combination of LiDFOB, LiBOB, LiPO2F2, LiPF6, LiBF4, LiN(SO2F)2, LiN(SO2C2F5)2, LiCF3SO3, LiC4F9O3, LiC6H5SO3, LiSCN, LiB(C2O4)2, and LiDFOP. The amount of the first additive lithium salt may be greater than the amount of the second additive lithium salt.
[0022] It can contain a first additive lithium salt and a second additive lithium salt in a weight ratio of 3:1 to 5:1.
[0023] The positive electrode may contain a positive electrode active material, and the positive electrode active material may include LiCoO2, LiNi, etc. x Co y Mn z O2 (x, y, and z are each independent real numbers from 0 to 1, where x + y + z = 1), LiNi x Coy Al z O2 (x, y, and z are each independent real numbers from 0 to 1, where x + y + z = 1), LiFePO4, sulfur, or any combination thereof.
[0024] Positive electrode active materials may include LiNi x Co y Mn z O2 (x, y, and z are each independent real numbers from 0 to 1, 0.8 ≤ x < 1, x + y + z = 1), LiNi x Co y Al z O2 (x, y, and z are each independent real numbers from 0 to 1, 0.8 ≤ x < 1, x + y + z = 1) or a combination thereof.
[0025] A method for preparing lithium metal integrated with a porous polymer carrier membrane loaded with an additive lithium salt, according to another embodiment, includes: mixing an organic solvent, a polymer, and an additive lithium salt to obtain a polymer solution, coating the polymer solution onto a lithium metal surface, and drying the polymer solution coated on the lithium metal surface.
[0026] The additives, lithium salts and polymers, in the porous polymer carrier membrane can be as described above.
[0027] The polymer solution can be coated on the lithium metal surface to a thickness ranging from 30 μm to 80 μm.
[0028] Based on the total amount of the polymer solution (100% by weight), the additive lithium salt can be included in an amount ranging from 2% to 20% by weight.
[0029] The additive lithium salt includes a first additive lithium salt and a second additive lithium salt. The first additive lithium salt may include LiNO3. The second additive lithium salt may include at least one or any combination of LiDFOB, LiBOB, LiPO2F2, LiPF6, LiBF4, LiN(SO2F)2, LiN(SO2C2F5)2, LiCF3SO3, LiC4F9O3, LiC6H5SO3, LiSCN, LiB(C2O4)2, and LiDFOP. The amount of the first additive lithium salt may be greater than the amount of the second additive lithium salt.
[0030] It can contain a first additive lithium salt and a second additive lithium salt in a weight ratio of 3:1 to 5:1.
[0031] It can contain organic solvents and additive lithium salts in a 1:1 weight ratio.
[0032] The mixing of organic solvents, polymers, and additive lithium salts can be carried out at temperatures ranging from 30°C to 50°C.
[0033] Drying the polymer solution coated on the lithium metal surface can be carried out under vacuum conditions at a temperature ranging from 80°C to 100°C for 6 to 24 hours.
[0034] The lithium metal battery according to the implementation scheme includes a lithium metal anode integrated with a porous polymer carrier membrane loaded with lithium salt additives. Even in solvents with extremely low solubility, trace amounts of lithium salt can be continuously dissolved and electrochemically generated, thereby significantly improving the cycle life characteristics of the lithium metal battery. Attached Figure Description
[0035] Figure 1 This is a schematic diagram illustrating a method for manufacturing a lithium metal anode integrated with a porous polymer carrier membrane loaded with additive lithium salts, according to an embodiment.
[0036] Figure 2 Scanning electron microscope (SEM) images showing the microstructure of the polymer film used in Comparative Example 1.
[0037] Figure 3 An energy dispersive X-ray (EDX) image showing the microstructure of the polymer film used in Comparative Example 1 is shown.
[0038] Figure 4 and Figure 5 The images shown are scanning electron microscope (SEM) images of the microstructure of the polymer carrier membrane used in Example 4.
[0039] Figure 6 An energy dispersive X-ray spectroscopy (EDX) image showing the microstructure of the polymer carrier film used in Example 4 is shown.
[0040] Figure 7 and Figure 8 The images shown are scanning electron microscope (SEM) images of the microstructure of the polymer carrier membrane used in Example 6.
[0041] Figure 9 An energy dispersive X-ray spectroscopy (EDX) image showing the microstructure of the polymer carrier film used in Example 6 is shown.
[0042] Figure 10 A graph showing the linear scan potential curves of the batteries according to Comparative Example 3 and Example 8.
[0043] Figure 11 The graph shows the cyclic voltammetry curves of the batteries from Comparative Examples 3 and 8.
[0044] Figure 12 The graph shows the AC impedance of the batteries in Comparative Examples 2 and 7.
[0045] Figure 13 and Figure 14 The images shown are scanning electron microscope (SEM) images of the lithium metal anode of the battery according to Comparative Example 4 in a charged state.
[0046] Figure 15 and Figure 16 The images shown are scanning electron microscope (SEM) images of the lithium metal anode of the battery according to Example 9 in a charged state.
[0047] Figures 17A to 17D The figures show the elemental composition as displayed in the X-ray photoelectron spectroscopy and X-ray photoelectron spectroscopy analysis of the lithium anode surface of the battery according to Comparative Example 4 in the charging state.
[0048] Figures 18A to 18D The graphs show the elemental composition as shown in the X-ray photoelectron spectroscopy and X-ray photoelectron spectroscopy analysis of the lithium anode surface of the battery according to Example 9 in the charging state.
[0049] Figures 19A to 19C The graphs are respectively showing the amount of residual lithium nitrate in the polymer carrier film according to the battery cycling process according to Example 9, wherein Figure 19A Before the loop, Figure 19B After the transformation into a cycle, and Figure 19C After 80 cycles.
[0050] Figure 20 This is a graph showing the direct current (DC) polarization curve of the battery according to Comparative Example 2.
[0051] Figure 21 This is a graph showing the DC polarization curve of the battery according to Example 7.
[0052] Figure 22 A graph showing the cycle characteristics (1.0 C) of the batteries according to Comparative Examples 7 and 12 to 14.
[0053] Figure 23 A graph showing the cycle characteristics (1.0 C) of the batteries according to Comparative Example 8 and Example 15.
[0054] Figure 24 A graph showing the cycle characteristics (1.0 C) of the batteries according to Comparative Examples 4 to 6 and Examples 9 to 11.
[0055] Figure 25A graph showing the cycle characteristics of the batteries according to Comparative Example 4, Comparative Example 10 and Example 9.
[0056] Figure 26 This is an example diagram of a lithium metal battery.
[0057] The accompanying drawings described herein are for illustrative purposes only and are not intended to limit the scope of the invention in any way.
[0058] [Explanation of reference numerals in the attached figures] 11 Lithium metal batteries 12 Lithium metal layer as negative electrode 13 Positive electrode 14. Diaphragm 15 Battery casing Detailed Implementation
[0059] In this specification, the terms first, second, and third are used to describe various technologies, components, regions, layers, and / or portions, but are not limited thereto. The terms are used only to distinguish any component, assembly, region, layer, or portion from other components, assemblies, regions, layers, or portions. Therefore, without departing from the scope of this invention, the first component, assembly, region, layer, or portion described below may be referred to as a second component, assembly, region, layer, or portion.
[0060] The specific terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the invention. Unless otherwise expressly stated otherwise, the singular form used herein includes the plural form as well. The terms “comprising” or “including” as used in the specification mean that a particular feature, region, integer, step, operation, element, and / or component is embodied, and do not exclude other particular features, regions, integers, steps, operations, elements, and / or components.
[0061] When any part is referred to as "on" or "above" other parts, it may be directly on or above the other parts, or it may involve different parts in between. Conversely, when any part is referred to as "directly on" other parts, no other parts are inserted in between.
[0062] Unless otherwise defined, all terms used herein (including technical and scientific terms) shall have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. Unless otherwise defined, commonly used predefined terms shall be further interpreted as having meanings consistent with relevant technical literature and this invention, and shall not be construed as having idealized or overly formal meanings.
[0063] As used herein, the term "combination thereof" as described in the Markush form refers to one or more mixtures or combinations of components selected from those described in the Markush form, and includes at least one selected from the components. In this invention, terms such as "A or B," "at least one of A and B," "at least one of A or B," "A, B or C," "at least one of A, B and C," "at least one of A, B or C," "at least one of A, B or C or a combination thereof," and "at least one of A, B or C or any combination thereof" can include any one or all possible combinations of the items commonly listed in the respective phrase.
[0064] Furthermore, as used herein, unless otherwise specifically defined, "*" refers to a part connected to the same or different atoms or chemical formulas.
[0065] The invention will now be described more fully, with embodiments thereof shown. Those skilled in the art will recognize that modifications can be made to the described embodiments in various ways without departing from the spirit or scope of the invention.
[0066] An embodiment of the present invention provides a lithium metal battery comprising a lithium metal negative electrode integrated with a polymer carrier membrane, wherein the polymer carrier membrane stores additive lithium salts that can improve the performance of the lithium metal battery.
[0067] The polymer carrier membrane containing additive lithium salt according to an embodiment of the present invention is manufactured by coating a solution containing additive lithium salt and polymer onto a lithium metal surface by solution casting, followed by drying. The manufactured polymer carrier membrane is chemically and electrochemically stable with lithium metal, has a very thin thickness and low ionic conductivity resistance, and has a porous structure, which facilitates the impregnation of the electrolyte and the elution of the additive lithium salt.
[0068] The polymer carrier membrane according to embodiments of the present invention can load and contain additive lithium salts for lithium metal batteries in amounts exceeding the solubility limit of the electrolyte. The polymer carrier membrane can improve the cycle life characteristics of lithium metal batteries by enabling the use of additive lithium salts that are difficult due to their extremely low solubility in the electrolyte, or by providing additional additive lithium salts that are depleted during operation.
[0069] Furthermore, polymer carrier membranes are suitable for specific electrolyte and additive lithium salt compositions, and can also be applied to all electrolyte and additive lithium salt compositions that can have a positive effect in lithium metal batteries, even when the additive lithium salt exceeds its solubility limit.
[0070] The lithium metal battery 11 according to the embodiment includes a positive electrode 13, a lithium metal negative electrode 12 opposite to the positive electrode, and a separator 14 located between the positive and negative electrodes. The lithium metal negative electrode is integrated with a porous polymer carrier membrane, which loads an additive lithium salt (see [link to embodiment]). Figure 26 ).
[0071] These lithium metal batteries can be used in a variety of fields such as energy storage devices (e.g., portable devices), electric vehicles, and medium and large energy storage systems (ESS), and the concept also includes a variety of rechargeable batteries such as lithium-sulfur batteries and negative electrode-free batteries.
[0072] The term "integration" can mean that there is no separation between the porous polymer carrier membrane and the lithium metal layer coated with the porous polymer carrier membrane. This integration significantly achieves the aforementioned effects.
[0073] Specifically, a lithium metal anode integrated with a porous polymer carrier membrane loaded with an additive lithium salt may include a current collector, a lithium metal layer on the current collector, and a porous polymer carrier membrane loaded with the additive lithium salt and located on the surface of the lithium metal layer. The lithium metal layer and the porous polymer carrier membrane may be integrated and will not be physically separated from each other (after manufacturing).
[0074] In embodiments of the invention, a polymer carrier membrane comprising an additive lithium salt for improving the performance of a lithium metal battery is manufactured in an integral form with lithium metal. The polymer carrier membrane manufactured in this way has a porous structure, which is beneficial for electrolyte impregnation and elution of the loaded additive lithium salt. Furthermore, the polymer carrier membrane can be manufactured to a relatively thin thickness of 5 μm or less (e.g., 3 μm to 5 μm), resulting in a very small increase in internal resistance of the battery and minimizing the decrease in energy density per unit volume. As the loaded additive lithium salt, various salts known to improve the performance of lithium metal batteries can be used, and the loaded salt can be continuously eluted in extremely small amounts (even in solvents with extremely low solubility) and act electrochemically, thereby improving the cycle life characteristics of the lithium metal battery.
[0075] For example, the additive lithium salt may include at least one or any combination of LiNO3, LiDFOB, LiBOB (lithium di(oxalate)borate), LiPO2F2, LiPF6, LiBF4, LiN(SO2F)2, LiN(SO2C2F5)2, LiCF3SO3, LiC4F9O3, LiC6H5SO3, LiSCN, LiB(C2O4)2, and LiDFOP (lithium difluoro(oxalate)phosphate).
[0076] Specifically, the additive lithium salt may include a first additive lithium salt and a second additive lithium salt. The first additive lithium salt may include LiNO3, and the second additive lithium salt may include at least one or any combination of LiDFOB, LiBOB, LiPO2F2, LiPF6, LiBF4, LiN(SO2F)2, LiN(SO2C2F5)2, LiCF3SO3, LiC4F9O3, LiC6H5SO3, LiSCN, LiB(C2O4)2, and LiDFOP. The amount of the first additive lithium salt may be greater than the amount of the second additive lithium salt. For example, lithium nitrate (the first additive lithium salt), which is known to form an excellent film on the surface of lithium metal, and lithium difluoro(oxalate)borate (the second additive lithium salt), which is also known to form an excellent film and contribute to stable charging / discharging of the high-voltage working positive electrode, can be used as the additive lithium salt.
[0077] At this point, the first additive lithium salt and the second additive lithium salt can be contained in a weight ratio of 3:1 to 5:1, for example, in a weight ratio of 4:1.
[0078] Meanwhile, based on the total amount (100 wt%) of the porous polymer carrier membrane, the additive lithium salt may be included in an amount of 2 wt% to 20 wt%, for example 2 wt% to 15 wt%, for example 2 wt% to 10 wt%, for example 2.5 wt% to 10 wt%.
[0079] When the additive lithium salt is controlled to the above composition, the manufactured porous polymer carrier membrane can be integrated into a lithium metal layer with a relatively thin thickness very easily.
[0080] The porous polymer carrier membrane may also contain a polymer, wherein the polymer may include at least one or any combination thereof of poly(vinylidene fluoride-hexafluoropropylene) copolymer (PVdF-HFP), polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), polymethyl methacrylate (PMMA), polyethylene oxide (PEO), polypropylene (PP), polyimide (PI), polyamide-imide (PAI), polystyrene (PS), polyvinyl chloride (PVC), polyether ether ketone (PEEK), and polyester sulfone (PES).
[0081] For example, the composition of porous polymer carrier membranes can utilize poly(vinylidene fluoride-co-hexafluoropropylene) copolymer (PVdF-HFP, trade name: Kynar) polymers with excellent electrochemical stability, ensuring no decomposition reaction occurs during lithium metal battery operation and good compatibility with various electrolytes used in rechargeable lithium batteries. Porous polymer carrier membranes (whereby additive lithium salts are loaded in an integrated form with the lithium metal) can be readily fabricated by mixing the polymer with additive lithium salts and directly coating it onto the surface of lithium metal using solution casting.
[0082] Lithium metal integrated with a porous polymer carrier membrane can be used in electrolytes with specific compositions, as well as in electrolytes with various compositions where the addition of lithium salts has a positive impact on cycle life characteristics.
[0083] For example, electrolytes can be prepared by mixing lithium salts with non-aqueous organic solvents, and non-aqueous organic solvents can be prepared by mixing at least one or any combination of carbonate organic solvents, ether organic solvents, sulfonamide solvents, and fluorinated organic solvents.
[0084] The lithium salt used in the electrolyte may include at least one of LiN(SO2F)2, LiN(SO2C2F5)2, LiN(CF3SO2)2, LiPF6, LiBF4, LiClO4, LiCF3SO3, LiC4F9O3, LiC6H5SO3, LiSCN, LiB(C2O4)2 and LiDFOP.
[0085] The ether-based organic solvents used in the electrolyte may include at least one or any combination of 1,2-dimethoxyethane, 1,3-dioxolane, and tetrahydrofuran. The carbonate-based organic solvents may include at least one or any combination of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, fluoroethylene carbonate, difluoroethylene carbonate, dimethyl fluorocarbonate, and methyl ethyl fluorocarbonate. The sulfonamide solvents may include at least one or any combination of N,N-dimethylfluorosulfonamide, N,N-dimethyltrifluoromethanesulfonamide, N-butylN,N,N-trimethylsulfonamide, and N-butyl-N-methyl-trifluoromethanesulfonamide. Fluorinated organic solvents may include at least one or any combination thereof, of 1,1,2,2-tetrafluoroethyl-1H,1H,5H-octafluoropentyl ether (TFOFE), 1,1,2,2-tetrafluoroethyl-2,2,2,3-tetrafluoropropyl ether (TTE), bis(2,2,2-trifluoropropyl) ether (BTFE), 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether (TFTFE), methoxynonfluorobutane (MOFB), and ethoxynonfluorobutane (EOFB).
[0086] For example, the thickness of the porous polymer support membrane can be 5 μm or less, such as 3 μm to 5 μm.
[0087] The lithium metal anode comprises a current collector (e.g., copper), a lithium metal layer, and a porous polymer carrier film. The thickness of the porous polymer carrier film should be controlled within the aforementioned range to facilitate control over the thickness of both the lithium metal layer and the current collector. By controlling the thickness of each layer constituting the lithium metal anode in this way, the final thickness of the manufactured lithium metal anode can be easily controlled from 5 μm to 200 μm, for example, from 10 μm to 100 μm, from 10 μm to 50 μm, or from 10 μm to 30 μm. This thickness control can significantly improve the cycle characteristics of lithium metal batteries including the lithium metal anode.
[0088] The positive electrode in a lithium metal battery contains a positive electrode active material, which is a compound capable of reversible insertion and extraction of lithium, and specifically may include lithium iron phosphate.
[0089] The positive electrode active material is a compound capable of reversible lithium insertion and extraction, and specifically may include lithium metal oxides comprising at least one or any combination of cobalt, manganese, nickel, phosphorus, iron, sulfur, and aluminum. More specifically, the lithium metal oxide may include at least one or any combination of lithium manganese-based oxides, lithium cobalt-based oxides, lithium nickel-based oxides, lithium iron phosphate-based oxides, lithium nickel manganese-based oxides, lithium nickel cobalt-based oxides, lithium manganese cobalt-based oxides, lithium nickel manganese cobalt-based oxides, lithium nickel manganese cobalt-based oxides, lithium nickel manganese aluminum oxides, and lithium nickel cobalt transition metal (M) oxides.
[0090] For example, positive electrode active materials may include LiCoO2 and LiNi. x Co y Mn z O2 (x, y, and z are each independent real numbers from 0 to 1, where x + y + z = 1), LiNi x Co y Al z O2 (x, y, and z are each independent real numbers from 0 to 1, where x + y + z = 1), LiFePO4, sulfur, or any combination thereof.
[0091] In particular, the lithium metal battery according to the embodiment can exhibit excellent compatibility with high-nickel (high-Ni) cathode active materials, which can improve the battery's capacity characteristics and stability. Therefore, the cathode active material can include LiNi. x Co y Mn z O2 (x, y, and z are each independent real numbers from 0 to 1, 0.8 ≤ x < 1, x + y + z = 1), LiNi x Co y Al zO2 (x, y, and z are each independent real numbers from 0 to 1, 0.8 ≤ x < 1, x + y + z = 1) or a combination thereof.
[0092] Specifically, the positive electrode may include a positive current collector and a layer of positive active material formed on the positive current collector.
[0093] The positive current collector can be made of stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel that has been surface-treated with carbon, nickel, titanium, silver, etc.
[0094] The thickness of the positive current collector can range from 3 μm to 500 μm.
[0095] The positive electrode active material layer may also contain adhesives and / or conductive materials.
[0096] The separator separates the negative and positive electrodes and provides a channel for the movement of lithium ions. There are no particular restrictions, as long as it is a separator commonly used in rechargeable lithium batteries.
[0097] According to another embodiment, a method is provided for preparing lithium metal integrated with a porous polymer carrier membrane loaded with an additive lithium salt. The method includes: mixing an organic solvent, a polymer, and an additive lithium salt to obtain a polymer solution; coating the polymer solution onto a lithium metal surface; and drying the polymer solution coated on the lithium metal surface.
[0098] The additive lithium salt or polymer can be the same as described above.
[0099] The polymer solution can be coated onto the lithium metal surface to a thickness of 30 μm to 80 μm. By coating the polymer solution to this thickness, the thickness of the final porous polymer carrier membrane after drying can be easily controlled to 5 μm or less, for example, 3 μm to 5 μm.
[0100] For example, the mixing of organic solvents, polymers, and additive lithium salts can be carried out at 30°C to 50°C.
[0101] For example, drying can be carried out under vacuum conditions at a temperature of 80°C to 100°C for 6 to 24 hours.
[0102] By controlling the process conditions as described above, lithium metal anodes with better quality can be manufactured.
[0103] The following embodiments illustrate implementations of the present invention in more detail. However, the following embodiments are merely examples of the present invention, and the present invention is not limited to the following embodiments.
[0104] Example Preparation of electrolytes Example 1: Sulfonamide electrolytes A sulfonamide liquid electrolyte was prepared by mixing dimethylfluorosulfonamide, which serves as a sulfonamide solvent, and lithium bis(fluorosulfonyl)imide (LiFSI) in a 3:1 molar ratio.
[0105] Example 2: Carbonate electrolyte for lithium metal batteries The carbonate electrolyte for lithium metal batteries is prepared by dissolving 0.8 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), 0.2 M lithium difluoro(oxalate)borate (LiDFOB), and 0.05 M lithium hexafluorophosphate (LiPF6) in an organic solvent, which is prepared by mixing fluoroethylene carbonate (FEC) (a cyclic carbonate solvent) and ethyl methyl carbonate (EMC) (a linear solvent) in a volume ratio of 25 / 75.
[0106] Example 3: Carbonate electrolyte for lithium metal batteries Carbonate electrolytes for lithium metal batteries are prepared by dissolving 1.15 M lithium hexafluorophosphate (LiPF6) in a mixed organic solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) in a volume ratio of 3 / 5 / 2, and then adding 5% by weight of fluoroethylene carbonate (FEC).
[0107] Manufacturing of lithium metal anodes Example 4: Lithium anode integrated with a polymer carrier membrane containing lithium nitrate The polymer solution was prepared by adding PVdF-HFP polymer and lithium nitrate to a dimethylacetamide organic solvent at 10% by weight, and then stirring at 45°C for 24 hours. The prepared solution was coated onto a lithium metal surface to a thickness of 50 μm using a doctor blade and then dried under vacuum at 90°C for 24 hours to produce a porous polymer support membrane containing lithium nitrate and with a thickness of less than or equal to 5 μm. Figure 1 A method for manufacturing a lithium anode integrated with a polymer carrier membrane containing lithium nitrate is shown.
[0108] Example 5: Lithium anode integrated with a polymer carrier membrane containing lithium difluoro(oxalate)borate The polymer solution was prepared by adding PVdF-HFP polymer and lithium difluoro(oxalate)borate salt, each in an amount of 10% by weight, to a dimethylacetamide organic solvent, and then stirring at 45°C for 24 hours. Subsequently, a porous polymer fiber protective layer containing lithium difluoro(oxalate)borate and having a thickness of less than or equal to 5 μm was manufactured in the same manner as in Example 4.
[0109] Example 6: Lithium anode integrated with a polymer carrier membrane containing lithium nitrate and lithium difluoro(oxalate)borate PVdF-HFP polymer, lithium nitrate, and lithium difluoro(oxalate)borate were added to a dimethylacetamide organic solvent in amounts of 10%, 10%, and 2.5% by weight, respectively, and then stirred at 45°C for 24 hours to prepare a polymer solution. Subsequently, a porous polymer fiber protective layer containing lithium nitrate and lithium difluoro(oxalate)borate with a thickness of less than or equal to 5 μm was prepared in the same manner as in Example 4.
[0110] Comparative Example 1: Lithium Anode Integrated with PVDF-HFP Polymer Membrane 10% by weight of PVdF-HFP polymer was added to a dimethylacetamide organic solvent and stirred at 45°C for 24 hours to prepare a polymer solution. The prepared solution was coated onto a lithium metal surface to a thickness of 5 μm or less using a doctor blade and then dried under vacuum at 90°C for 24 hours to fabricate a lithium anode integrated with a polymer film of 5 μm or less in thickness.
[0111] Fabrication of a porous polymer membrane separated from the lithium anode Comparative Example 9: Polymer film containing additive lithium salt that is not integrated with lithium metal PVdF-HFP polymer and lithium nitrate were added to a dimethylacetamide organic solvent at 10% by weight, and then stirred at 45°C for 24 hours to prepare a polymer solution. The prepared solution was coated onto a polyethylene terephthalate (PET) release membrane to a thickness of 50 μm using a doctor blade, and then dried under vacuum at 90°C for 24 hours to produce a separated porous polymer carrier membrane with a thickness of approximately 5 μm.
[0112] Battery cell manufacturing Example 7: A button-type lithium-ion symmetric battery using a lithium anode comprising a sulfonamide electrolyte and a lithium nitrate carrier membrane. A coin-type lithium-ion symmetric battery cell (lithium / electrolyte / lithium) is fabricated using the electrolyte according to Example 1 and the lithium electrode integrated with the carrier membrane according to Example 4. Here, a polyethylene separator is used to separate the two electrodes.
[0113] Example 8: A button-type lithium / stainless steel (SUS) battery using a lithium anode comprising a sulfonamide electrolyte and a lithium nitrate carrier membrane. To analyze the electrochemical properties of the fabricated polymer fiber membrane containing lithium nitrate, a coin cell was fabricated using a lithium anode and a stainless steel (SUS) electrode. Example 1 was used as the electrolyte, and Example 4 was used as the lithium metal anode. Lithium metal was used as both the reference and counter electrodes, and the SUS electrode was used as the working electrode. A polyethylene separator was used to separate the two electrodes.
[0114] Examples 9 to 15: Button-type lithium metal batteries using various electrolytes and carrier membranes (see Table 1) The coin-type lithium metal battery cell is fabricated using the lithium metal anode and electrolyte provided in Table 1. A high-nickel cathode active material (LiNi) is used as the cathode. 0.8 Co 0.1 Mn 0.1 O2). Here, the thickness of the lithium metal used as the negative electrode is 20 μm (the thickness of the copper (Cu) current collector is 10 μm), and the capacity per unit area of the positive electrode is 4.0 mAh / cm². 2 The electrolyte is 6 g / Ah, and a polyethylene membrane is used to separate the negative and positive electrodes.
[0115] Table 1 Comparative Example 2: Button-type lithium-ion symmetric battery using sulfonamide electrolyte The electrolyte from Example 1 was used to fabricate a button-type lithium-ion symmetric battery cell (lithium / electrolyte / lithium). Here, a polyethylene separator was used to separate the two electrodes.
[0116] Comparative Example 3: Button-type lithium / SUS battery using sulfonamide electrolyte A coin cell was fabricated using a lithium anode and a stainless steel (SUS) electrode. Example 1 was used as the electrolyte, and Comparative Example 1 was used as the lithium metal anode. Lithium metal was used as both the reference and counter electrodes, and the SUS electrode was used as the working electrode. A polyethylene separator was used to separate the two electrodes.
[0117] Comparative Example 4: Button-type lithium metal battery using sulfonamide electrolyte A coin-type lithium metal battery cell was fabricated using a lithium metal anode and the electrolyte from Example 1. A high-nickel cathode active material (LiNi) was used as the cathode. 0.8 Co 0.1 Mn 0.1 O2). Here, the thickness of the lithium metal used as the negative electrode is 20 μm (the thickness of the Cu current collector is 10 μm), and the capacity per unit area of the positive electrode is 4.0 mAh / cm². 2 The electrolyte is 6 g / Ah, and a polyethylene membrane is used to separate the negative and positive electrodes.
[0118] Comparative Example 5: A button-type lithium metal battery using a sulfonamide electrolyte and including a polymer film containing unloaded lithium salts. A coin-type lithium metal battery cell was fabricated using the lithium metal anode of Comparative Example 1 and the electrolyte of Example 1. A high-nickel cathode active material (LiNi) was used as the cathode. 0.8 Co 0.1 Mn 0.1 O2). Here, the thickness of the lithium metal used as the negative electrode is 20 μm (the thickness of the Cu current collector is 10 μm), and the capacity per unit area of the positive electrode is 4.0 mAh / cm². 2 The electrolyte is 6 g / Ah, and a polyethylene membrane is used to separate the negative and positive electrodes.
[0119] Comparative Example 6: Button-type lithium metal battery using a sulfonamide electrolyte containing lithium nitrate A coin-type lithium metal battery cell was manufactured using a lithium metal anode and an electrolyte prepared by adding 0.05% by weight of lithium nitrate to the electrolyte of Example 1. A high-nickel cathode active material (LiNi) was used as the cathode. 0.8 Co 0.1 Mn 0.1 O2). Here, the thickness of the lithium metal used as the negative electrode is 20 μm (the thickness of the Cu current collector is 10 μm), and the capacity per unit area of the positive electrode is 4.0 mAh / cm². 2 The electrolyte is 6 g / Ah, and a polyethylene membrane is used to separate the negative and positive electrodes.
[0120] Comparative Example 7: Button-type lithium metal battery using a carbonate electrolyte for lithium metal batteries A coin-type lithium metal battery cell was fabricated using a lithium metal anode and the electrolyte from Example 2. A high-nickel cathode active material (LiNi) was used as the cathode. 0.8 Co 0.1 Mn 0.1 O2). Here, the thickness of the lithium metal used as the negative electrode is 20 μm (the thickness of the Cu current collector is 10 μm), and the capacity per unit area of the positive electrode is 4.0 mAh / cm². 2 The electrolyte is 6 g / Ah, and a polyethylene membrane is used to separate the negative and positive electrodes.
[0121] Comparative Example 8: Button-type lithium metal battery using a carbonate electrolyte for lithium-ion batteries A coin-type lithium metal battery cell was fabricated using a lithium metal anode and the electrolyte of Example 3. A high-nickel cathode active material (LiNi) was used as the cathode. 0.8 Co 0.1 Mn0.1 O2). Here, the thickness of the lithium metal used as the negative electrode is 20 μm (the thickness of the Cu current collector is 10 μm), and the capacity per unit area of the positive electrode is 4.0 mAh / cm². 2 The electrolyte is 6 g / Ah, and a polyethylene membrane is used to separate the negative and positive electrodes.
[0122] Comparative Example 10: A button-type lithium metal battery using a sulfonamide electrolyte and including an additive carrier film not integrated with lithium metal. The separate (isolated) carrier film of Comparative Example 9 was placed facing the lithium metal, and then used with the electrolyte of Example 1 to fabricate a coin-type lithium metal battery cell. A high-nickel positive electrode active material (LiNi) was used as the positive electrode. 0.8 Co 0.1 Mn 0.1 O2). Here, the thickness of the lithium metal used as the negative electrode is 20 μm (the thickness of the Cu current collector is 10 μm), and the capacity per unit area of the positive electrode is 4.0 mAh / cm². 2 The electrolyte is 6 g / Ah, and a polyethylene membrane is used to separate the negative and positive electrodes.
[0123] Experimental Example 1. Microstructure analysis of polymer films loaded with lithium salt additives Figures 2 to 9 Microstructure images of the fabricated polymer films, analyzed by scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX), are shown. The analysis results indicate that a porous structure was observed when the additive lithium salt was loaded as in Examples 4 and 6, but a dense structure was observed when no additive lithium salt was loaded. EDX analysis confirmed that N and B elements, representing the additive lithium salt, were uniformly present with C and F elements, representing the PVDF-HFP polymer. Cross-sectional analysis confirmed that the polymer films loaded with the additive lithium salt had a porous structure and a thickness of less than or equal to 5 μm.
[0124] 2. Confirmation of the electrochemical behavior of polymer films loaded with lithium nitrate The electrochemical behavior of the polymer support film loaded with lithium nitrate (Example 4) was examined by fabricating each battery cell using lithium metal and SUS electrodes prepared in Comparative Examples 3 and 8 (which underwent linear sweep current method at 1 mV / s at room temperature). The results showed that... Figure 10 In addition, Figure 11 Cyclic voltammetry results are shown for a battery cell with the same structure as described above at 0.1 mV / s and room temperature. (Reference) Figure 10 and Figure 11When a polymer support membrane containing lithium nitrate is applied, a current of approximately 1.7 V (known as the reduction potential of lithium nitrate) is generated, thus confirming that lithium nitrate loaded on the polymer membrane plays an electrochemical role.
[0125] 3. Confirmation of changes in electrochemical resistance when using membranes containing lithium nitrate. To examine the change in the internal resistance of the battery cell when a polymer carrier film loaded with lithium nitrate (Example 4) is applied, the internal resistance of the lithium-electrolyte-lithium battery cells of Comparative Examples 2 and 7 was measured at room temperature using an AC impedance analyzer. The results show... Figure 12 The AC impedance was measured by applying a 5 mV voltage in the range of 1,000,000 Hz to 1 Hz. The measurement results confirmed that, compared with Comparative Example 2, Example 7 exhibited a slight increase in battery internal resistance, but remained at almost the same level, which confirms that the polymer carrier film with a porous structure does not interfere with the ionic conductivity within the battery cell.
[0126] 4. Confirmation of changes in lithium deposition morphology in sulfonamide electrolytes when using polymer carrier membranes containing lithium nitrate. The lithium metal battery cells manufactured through Comparative Examples 4 and 9 were charged once at a 0.1 C rate, and then disassembled while charged to remove the lithium metal anode. Their microstructure was analyzed by SEM, and the results showed... Figures 13 to 16 Image analysis confirmed that the lithium electrodeposited in Example 9 had a denser and more uniform morphology compared to the lithium deposited in Comparative Example 4. This confirms that when a polymer support film loaded with lithium nitrate is applied in a sulfonamide electrolyte, the electrodeposited lithium exhibits a more uniform morphology.
[0127] 5. Analysis of lithium anode film composition when using polymer support membranes containing lithium nitrate Table 2 Figures 17A to 17D and Figures 18A to 18D The results of X-ray photoelectron spectroscopy analysis of the surface of the lithium metal anode obtained after cycling the lithium metal battery cells of Comparative Examples 4 and 9 at 0.1 C for 5 times are shown. When a polymer support film containing lithium nitrate is included, it is confirmed that the proportions of Li₂O, Li₃N, etc., are significantly increased due to the formation of the lithium nitrate film. As a result of elemental analysis, Example 9 shows a significant decrease in C content, thereby inhibiting film formation through the decomposition of the sulfonamide electrolyte solvent in Example 9. The increase in the proportions of elements such as N, F, and S in Comparative Example 4 is due to the decomposition of the sulfonamide electrolyte solvent.
[0128] Table 2 6. Ion chromatography was used to confirm the consumption of lithium nitrate in the polymer membrane. Table 3 and Figures 19A to 19C The results show the results of ion chromatography to measure the amount of residual lithium nitrate within the battery cell after charging and discharging the lithium metal battery cell manufactured in Example 9 during a predetermined cycle. Ion chromatography was performed on the solution obtained by dissociating all battery components in water after disassembling the charged and discharged battery cell. The analysis confirmed that lithium nitrate decreased with charging and discharging. This confirms that the loaded lithium nitrate is consumed during battery operation, thus acting as an additive within the battery cell.
[0129] Table 3 7. Evaluation results of lithium-symmetric cells when using polymer films loaded with lithium nitrate. Figure 20 and Figure 21 To achieve this, 1.5 mA / cm² was alternately applied to the lithium symmetric battery cells manufactured through Comparative Examples 2 and 7. 2 The DC polarization curves were obtained by repeating lithium deposition / desorption cycles with a current of 2 hours. When a polymer carrier film containing lithium nitrate (Example 7) was applied, more stable cycling was observed than when it was not applied. In particular, the battery of Comparative Example 2 exhibited a short circuit after about 700 hours, while the battery of Example 7 remained stable even after 700 hours.
[0130] 8. Evaluation of cycle life characteristics of lithium metal batteries in carbonate electrolytes when polymer membranes are used. Figure 22 and Figure 23 Evaluation results for the lithium metal battery cells of Examples 7 and 8 and Examples 12 to 15 are shown when the charge and discharge rates are set to 1.0C. Subsequent results demonstrate that the performance of lithium metal batteries is improved when the polymer carrier film is applied to both the carbonate electrolyte of lithium metal batteries and conventional lithium-ion batteries. This confirms that the polymer carrier film according to embodiments of the present invention can be applied not only to specific electrolyte compositions but also to a wide variety of electrolyte compositions to improve performance.
[0131] Furthermore, based on the confirmation that performance varies depending on the type of additive lithium salt contained in the carrier film, it was confirmed that performance improvements can be expected even when loading other additive lithium salts besides lithium nitrate.
[0132] 9. Evaluation of cycle life characteristics of lithium metal batteries in sulfonamide electrolytes when polymer membranes are used. Figure 24Evaluation results for the lithium metal battery cells of Comparative Examples 4 to 6 and Examples 9 to 11 are shown when the charge and discharge rates are set to 1.0C. The evaluation was conducted by setting the voltage within a range of 3.0 V to 4.25 V. By comparing with Comparative Examples 5 and 6, it was confirmed that the cycle life characteristics of the battery cell were significantly improved when the polymer carrier membrane according to an embodiment of the present invention was applied, compared to the case where lithium nitrate was added at the maximum solubility of the electrolyte (Comparative Example 5) or the case where a separate polymer membrane was used (Comparative Example 6). Therefore, it was confirmed that the additive lithium salt loaded within the polymer carrier membrane continuously plays a role during the operation of the lithium metal battery cell, thereby improving the cycle life characteristics.
[0133] 10. Comparative evaluation of cycle life when using polymer carrier membranes not integrated with the lithium metal anode. Figure 25 The results show the evaluation of the cycle performance of lithium metal battery cells based on whether the polymer carrier film is integrated, with the charge and discharge rates set to 1.0C. The evaluation was conducted by setting the voltage within the range of 3.0 V to 4.25 V. The carrier film not integrated with the lithium metal was manufactured to a thickness of approximately 7 μm. Compared to Comparative Example 4 without a carrier film, Comparative Example 10 using this carrier film exhibited higher cycle life characteristics due to the elution of lithium nitrate; however, due to the increased internal resistance within the battery cell, the initial capacity was significantly reduced, resulting in a significantly lower cycle life characteristic compared to Example 9 using the integrated polymer film. Therefore, it is confirmed that excellent cycle life characteristics are achieved when the carrier film is integrated with the lithium metal.
[0134] Although embodiments of the present invention have been described above, the present invention is not limited thereto, and various modifications can be made within the scope of the patent claims, the specific implementation of the embodiments, and the accompanying drawings, which also fall within the scope of the present invention.
[0135] Therefore, the scope of this invention is defined by the appended claims and their equivalents.
Claims
1. A lithium metal battery, the lithium metal battery comprising: positive electrode; The lithium metal anode is located opposite the positive electrode; as well as A separator, wherein the separator is located between the positive electrode and the lithium metal negative electrode; The lithium metal anode is integrated with a porous polymer carrier membrane, and the porous polymer carrier membrane is loaded with lithium salt additives.
2. The lithium metal battery according to claim 1, wherein, The additive lithium salt includes at least one or any combination thereof from LiNO3, LiDFOB, LiBOB, LiPO2F2, LiPF6, LiBF4, LiN(SO2F)2, LiN(SO2C2F5)2, LiCF3SO3, LiC4F9O3, LiC6H5SO3, LiSCN, LiB(C2O4)2, and LiDFOP.
3. The lithium metal battery according to claim 1, wherein, The porous polymer carrier membrane further comprises a polymer, and The polymer includes at least one or any combination thereof of poly(vinylidene fluoride-hexafluoropropylene) copolymer, polyvinylidene fluoride, polytetrafluoroethylene, polymethyl methacrylate, polyethylene oxide, polypropylene, polyimide, polyamide-imide, polystyrene, polyvinyl chloride, polyetheretherketone, and polyester sulfone.
4. The lithium metal battery according to claim 1, wherein, The thickness of the porous polymer carrier membrane is less than or equal to 5 μm.
5. The lithium metal battery according to claim 1, wherein, The additive lithium salt is contained in an amount ranging from 2% to 20% by weight, based on a total of 100% by weight of the porous polymer carrier membrane.
6. The lithium metal battery according to claim 1, wherein, The thickness of the lithium metal anode is in the range of 5 μm to 200 μm.
7. The lithium metal battery according to claim 1, wherein, Lithium metal anodes integrated with porous polymer support membranes containing lithium salts as additives include: Current collector; The lithium metal layer located on the current collector; and A porous polymer carrier membrane, wherein the porous polymer carrier membrane is coated on the surface of the lithium metal layer and loaded with an additive lithium salt; The lithium metal layer and the porous polymer carrier membrane are integrated.
8. The lithium metal battery according to claim 7, wherein, The thickness of the lithium metal layer is greater than the thickness of the current collector, and The thickness of the current collector is greater than the thickness of the porous polymer carrier membrane.
9. The lithium metal battery according to claim 1, wherein, The additive lithium salt includes a first additive lithium salt and a second additive lithium salt. The first additive lithium salt includes LiNO3, and The second additive lithium salt includes at least one or any combination of LiDFOB, LiBOB, LiPO2F2, LiPF6, LiBF4, LiN(SO2F)2, LiN(SO2C2F5)2, LiCF3SO3, LiC4F9O3, LiC6H5SO3, LiSCN, LiB(C2O4)2, and LiDFOP. The amount of the first additive lithium salt is greater than the amount of the second additive lithium salt.
10. The lithium metal battery according to claim 9, wherein, It contains a first additive lithium salt and a second additive lithium salt in a weight ratio of 3:1 to 5:
1.
11. The lithium metal battery according to claim 1, wherein, The positive electrode contains a positive electrode active material. The positive electrode active material includes LiCoO2 and LiNi. x Co y Mn z O2, LiNi x Co y Al z O2, LiFePO4, sulfur, or any combination thereof, wherein x, y, and z are each independent real numbers from 0 to 1, and x + y + z = 1.
12. The lithium metal battery according to claim 11, wherein, The positive electrode active material includes LiNi. x Co y Mn z O2, LiNi x Co y Al z O2 or a combination thereof, x, y and z are each independent real numbers from 0 to 1, 0.8≤x<1, x+y+z=1.
13. A method for preparing lithium metal integrated with a porous polymer support membrane containing a lithium salt as an additive, the method comprising: An organic solvent, polymer, and additive lithium salt are mixed to obtain a polymer solution. The polymer solution is coated onto the lithium metal surface, and The polymer solution coated on the lithium metal surface is dried.
14. The method for preparing lithium metal integrated with a porous polymer support membrane for loading lithium salt according to claim 13, wherein, The additive lithium salt includes at least one or any combination thereof from LiNO3, LiDFOB, LiBOB, LiPO2F2, LiPF6, LiBF4, LiN(SO2F)2, LiN(SO2C2F5)2, LiCF3SO3, LiC4F9O3, LiC6H5SO3, LiSCN, LiB(C2O4)2, and LiDFOP.
15. The method for preparing lithium metal integrated with a porous polymer support membrane for loading lithium salt according to claim 13, wherein, The porous polymer carrier membrane further comprises a polymer, and The polymer includes at least one or any combination thereof of poly(vinylidene fluoride-hexafluoropropylene) copolymer, polyvinylidene fluoride, polytetrafluoroethylene, polymethyl methacrylate, polyethylene oxide, polypropylene, polyimide, polyamide-imide, polystyrene, polyvinyl chloride, polyetheretherketone, and polyester sulfone.
16. The method for preparing lithium metal integrated with a porous polymer support membrane for loading lithium salt additives according to claim 13, wherein, The additive lithium salt is contained in an amount ranging from 2% to 20% by weight, based on a total of 100% by weight of the polymer solution.
17. The method for preparing lithium metal integrated with a porous polymer support membrane for loading lithium salt according to claim 13, wherein, The additive lithium salt includes a first additive lithium salt and a second additive lithium salt. The first additive lithium salt includes LiNO3, and The second additive lithium salt includes at least one or any combination of LiDFOB, LiBOB, LiPO2F2, LiPF6, LiBF4, LiN(SO2F)2, LiN(SO2C2F5)2, LiCF3SO3, LiC4F9O3, LiC6H5SO3, LiSCN, LiB(C2O4)2, and LiDFOP. The amount of the first additive lithium salt is greater than the amount of the second additive lithium salt.
18. The method for preparing lithium metal integrated with a porous polymer support membrane for loading lithium salt additives according to claim 17, wherein, It contains a first additive lithium salt and a second additive lithium salt in a weight ratio of 3:1 to 5:
1.
19. The method for preparing lithium metal integrated with a porous polymer support membrane for loading lithium salt according to claim 13, wherein, It contains organic solvent and lithium salt additive in a 1:1 weight ratio.
20. The method for preparing lithium metal integrated with a porous polymer support membrane for loading lithium salt according to claim 13, wherein, The mixing of organic solvents, polymers, and additive lithium salts is carried out at temperatures ranging from 30°C to 50°C, and The polymer solution coated on the lithium metal surface was dried under vacuum conditions at a temperature ranging from 80°C to 100°C for 6 to 24 hours.
Citation Information
Patent Citations
Method for producing organic sulfonic acid compound
KR1020250055406A
